2022
DOI: 10.1002/pc.26975
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the mechanical and thermal properties of polycarbonate composites reinforced by KH570/SA/SDBS modified wollastonite fibers

Abstract: In order to increase the applicability of wollastonite (Wo) in polycarbonate (PC) polymer, surface modification of Wo was carried out using different modifiers containing silane coupling agent KH570, stearic acid (SA), and sodium dodecylbenzene sulfonate. The physical, physic-chemical, and application properties of modified Wo were evaluated. Results showed that KH570 modified Wo had narrower particle size distribution, higher absolute zeta potential and were more evenly distributed. Scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The surface‐modified FA was examined as shown in Figure 2. It can be observed that a new peak at 1740 cm −1 , corresponding to the stretching vibration of CO in COO, 44,45 was present in KH570‐SA‐F but not in FA, indicating the successful surface modification for FA. Additionally, there were no differences observed at the peaks of 3450 and 1660 cm −1 in KH570‐SA‐F and FA, 46,47 which correspond to the stretching vibration and bending vibration of the free hydroxyl group.…”
Section: Resultsmentioning
confidence: 97%
“…The surface‐modified FA was examined as shown in Figure 2. It can be observed that a new peak at 1740 cm −1 , corresponding to the stretching vibration of CO in COO, 44,45 was present in KH570‐SA‐F but not in FA, indicating the successful surface modification for FA. Additionally, there were no differences observed at the peaks of 3450 and 1660 cm −1 in KH570‐SA‐F and FA, 46,47 which correspond to the stretching vibration and bending vibration of the free hydroxyl group.…”
Section: Resultsmentioning
confidence: 97%
“…Angel et al 28 used SA as a lubricant for favoring the interaction of polypropylene with the bentonite and decreasing the viscosity of the compounds, as well as polypropylene/calcium carbonate compounds 29 . Chen et al 30 used SA to enhance the applicability of wollastonite in polycarbonate. However, there have been no reports on the application of SA in the preparation of UHMWPE fibers by gel spinning.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] FRP composites are suitable for adequately transporting and storing cryogenic fluids. [8,9] The integrity and durability of composite materials depend upon humidity, [10][11][12][13] high [14][15][16][17][18][19] and low [20,21] temperatures, and cryogenic [22][23][24] conditions. Low-temperature fluids, such as liquid methane (À161 C), liquid nitrogen (À196 C), and liquid hydrogen (À252 C), are frequently kept in compacted form in cryogenic storage tanks.…”
Section: Introductionmentioning
confidence: 99%